PERSEPSI PENONTON TERHADAP PRODUCT PLACEMENT HONDA SUPER CUB PADA SERIAL ANIME SUPER CUB (E-Jurnal Medium, 2022)
Product placement is a way to increase promotion of a product by showing the product as if the appearance of that product is a part of story of a film or TV show. Super Cub is one of the anime which putting product placement in their show. The product that being promoted is Honda Super Cub. This research is purposing to know Super Cub audience’s perception of the Honda Super Cub product placement in the Super Cub anime by descriptive quantitative research. The result shows the audiences are getting good perception of the Honda Super Cub product placement. From all four indicators, attention and hope indicators are getting very good perception. Meanwhile interest indicator is getting medium score, and motivation indicator is getting low score.